1 + 1′ > 2: Heteronuclear Biatom Catalyst Outperforms Its Homonuclear Counterparts for CO Oxidation. Issue 9 (21st March 2019) - Li, Fengyu; Liu, Xinying; Chen, Zhongfang
Abstract: By means of density functional theory (DFT) computations, the CO/O2 adsorption and CO oxidation pathways on the biatom catalyst, namely the heteronuclear Fe1 Cu1 @C2 N, in comparison with its homonuclear counterparts Fe2 @C2 N and Cu2 @C2 N are systemically investigated. The reactions of O2 dissociation and CO oxidization with preadsorbed CO or O2 are comparably studied. The computations find that the heteronuclear species Fe1 Cu1 @C2 N possesses high stabilities and is feasible to be synthesized experimentally. More importantly, the heteronuclear Fe1 Cu1 @C2 N catalyst has even better catalytic activity toward CO oxidation than its homonuclear counterparts, especially, without suffering the CO‐poisoning problem. Considering the myriad of unexplored heteronuclear dimers that can be potentially anchored at appropriate supports, this work opens a new avenue and provides a useful guideline for further developing bimetal‐based nanocatalysts. Abstract : Beyond single‐atom catalysts (SACs), biatom catalysts, in which metal dimers are anchored on an appropriate substrate, have recently emerged as extended family members of SACs. Here, by means of density functional theory (DFT) computations, the performance of heteronuclear metal dimer Fe1 Cu1 anchored on the porous C2 N monolayer as a biatom catalyst for CO oxidation is demonstrated, outperforming its homonuclear counterparts.